COMPARATIVE ANALYSIS OF OUTCOME AFTER MEDICAL THERAPY ALONE VERSUS INCOMPLETE REVASCULARIZATION ALONG WITH MEDICAL THERAPY IN PATIENTS WITH MULTI-VESSEL CORONARY ARTERY DISEASE - MAHMOOD , K; JAVAID , I; ADEEB , O; HASHMI , KA (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in the Department of Cardiology, Chaudhry Pervez Elahi Institute of Cardiology, Multan, from 29-Jan-2022 to 28-Jul-2022 to compare the frequency of relief from angina after medical therapy alone versus incomplete revascularization along with medical therapy in local patients with multi-vessel coronary artery disease. A total of 60 patients were enrolled and randomly divided into groups I and II. Group I received standard medical therapy as per the operational definition. Group II underwent incomplete coronary artery re-vascularization – stent placement through PCI in the fluoroscopy suite. Post-IR, these patients also received standard medical therapy. All the patients were called for monthly follow-up. Patients having symptomatic relief from angina were placed in functional class II. Results showed that pain relief from angina was observed in 10 (16.67%) patients and not in 50 (83.33%). A group comparison of symptomatic relief from angina showed that relief was observed in 02 (6.70%) patients in group I and 08 (26.70%) patients in group II. This result was statistically significant, with a p-value of 0.038. Stratification was performed based on age, gender, diabetes, hypertension, smoking, and obesity. There was no association between these variables and angina relief in either group. It can be concluded that in multi-vessel coronary artery disease, incomplete revascularization and medical therapy are superior to medical therapy alone.